2021
DOI: 10.31014/aior.1992.04.03.385
|View full text |Cite
|
Sign up to set email alerts
|

Improved Seeds Adoption Among Smallholder Rice Farmers in Togo: The Case of NERICA in the Savannah Region

Abstract: The low adoption of new technologies, particularly improved seeds, remains a critical issue hampering the development of agriculture in many developing countries. The objective of this research is to identify the determinants of (i) the farmer’s knowledge,( ii) the adoption decision and (iii) the adoption intensity of NERICA rice varieties in the Togolese Savannah region. Probit and Tobit models were used to analyse data collected from 150 rice growers randomly selected. The results of the estimations showed t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Gender issues in agricultural technology adoption have long been researched, and the plurality of studies have revealed inconsistent data on the distinct roles men and women play in technology adoption (Yovo and Ganiyou, 2021). A household's size is simply a measure of labor availabili-ty.…”
Section: Human Capital Factorsmentioning
confidence: 99%
“…Gender issues in agricultural technology adoption have long been researched, and the plurality of studies have revealed inconsistent data on the distinct roles men and women play in technology adoption (Yovo and Ganiyou, 2021). A household's size is simply a measure of labor availabili-ty.…”
Section: Human Capital Factorsmentioning
confidence: 99%